Influence of Mn valence state and characteristic of TiO2 on the performance of Mn–Ti catalysts in ozone decomposition. Issue 22 (17th November 2017) - Kwon, Dong Wook; Kim, Geo Jong; Won, Jong Min; Hong, Sung Chang
ABSTRACT: The effects of physicochemical properties of Mn–Ti catalysts on O3 conversion were examined. The catalysts were prepared by a wet impregnation method that gave manganese supported on various commercial sources of TiO2 . The properties of the catalysts were studied using physicochemical techniques, including Brunauer–Emmett–Teller (BET) surface area analysis, X-ray diffraction (XRD), H2 temperature-programmed reduction (H2 -TPR), X-ray photoelectron spectroscopy (XPS), and thermal gravimetric analysis (TGA). The O3 decomposition tests of Mn–Ti catalysts with various manganese loadings revealed that the 10 wt% manganese catalyst exhibited optimal, excellent activity. The O3 conversion and Mn valence state of the Mn–Ti catalysts were different, depending on the structure of the TiO2 source. Increasing the O/Ti surface atomic ratio in TiO2 increased the Mn 3+ ratio. The Mn 3+ ratio directly affected the O3 decomposition activity of the Mn–Ti catalyst. When the Mn 3+ ratio was the largest, the catalyst showed the highest activity in O3 decomposition. The valence state of Mn exposed to the surface was a critical factor in O3 decomposition by Mn–Ti catalysts.